Type Synthesis of 5-DOF Series-parallel based on Single-opened-chain and Position and Orientation Characteristic Set - Bangcheng Zhang; Yage Wang; Yu Yao; Qifei Peng (Jixie chuandong)
A 5-DOF series-parallel robot is designed based on the single-opened-chain and position and orientation characteristic set， and the configuration synthesis and degrees of freedom of the 5-DOF series-parallel robot are calculated and analyzed to verify that the proposed mechanism meets the design requirements. The kinematics of the 5-DOF series-parallel robot is further discussed， and the position inverse solution of the parallel mechanism and the speed of the moving platform are analyzed. The Adams software is used to simulate the designed 5-DOF series-parallel robot to verify the feasibility of the mechanism. The results show that the proposed mechanism has the characteristics of relatively stable motion and large working space， which provides a reference basis for the multi-drive control of the 5-DOF series-parallel mechanism.